Obserwacje nietypowe - przypadek wielowymiarowy - Heilpern, Stanisław (Outliers - multidimensional case, 2005)
The paper is devoted to the outliers in multivariate data. It reviews selected methods of the detection of the multidimensional outliers. These are the methods based on the statistical inference using Mahalanobis distance and the preference relations and based on the descriptive and graphical methods. The robust estimation of the vector location and the covariance matrix, weakly reacting to the outliers, are studied. The Huber’s, Gnanadesikan-Kettenring’s and Cambell’s methods are presented and the affine invariant estimators obtained by the minimum volume ellipsoid and the minimum covariance matrix determinant methods are studied. The paper contains the examples illustrating presented methods. There are two tables with the critical values of the statistical tests used to the detection of the multidimensional outliers in the appendix.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 68-87